The reservoir characteristics of marine shale and its effect on the adsorption of methane in Northern Guizhou. (2nd November 2019) - Jiao, Baocheng; Ding, Wenlong; Gu, Yang; Xiao, Zikang; Shi, Siyu; Zhao, Gang; Liu, Tianshun
Abstract: The reservoir characteristics of the Lower Paleozoic marine shale in Fenggang block of northern Guizhou are evaluated from three aspects: gas-bearing characteristics, petrological characteristics and reservoir space by a series of experimental data. The effect of total organic carbon content, kerogen type and clay mineral content on shale adsorption capacity is discussed. The results show that the reservoir characteristics of the Wufeng-Longmaxi Formation shale in the study area are conducive to the enrichment of shale gas. In the case of quantitative clay minerals, the chlorite content has a significant adverse effect on the methane adsorption of the samples. The shale gas methane adsorption has an excellent increasing trend with the increase of total organic carbon content. The type II1 organic matter is more conducive to the adsorption of methane than the type I organic matter.